2021
DOI: 10.1186/s12902-020-00674-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between parity and metabolic syndrome and its components in normal-weight postmenopausal women in China

Abstract: Background Studies analyzing the association between parity and normal-weight metabolic syndrome (MetS) in postmenopausal women of normal weight remain limited, this study aimed to explore the association between parity and MetS among Chinese normal-weight postmenopausal women. Methods In total, 776 normal-weight undiagnosed type 2 diabetes postmenopausal women who visited the Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Med… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Similarly, data from the Dongfeng-Tongji cohort study show cross-sectionally a significant increasing trend in type 2 diabetes risk among women who had two, three, and four or more live births 46 . More recently, Shi et al 47 in a cross-sectional analysis of normal-weight undiagnosed type 2 diabetes postmenopausal women report that parity was not significantly associated with increased risk of metabolic syndrome. However, the odds of metabolic risk factor such abdominal obesity was significantly associated with multiparity in normal weight Chinese women 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, data from the Dongfeng-Tongji cohort study show cross-sectionally a significant increasing trend in type 2 diabetes risk among women who had two, three, and four or more live births 46 . More recently, Shi et al 47 in a cross-sectional analysis of normal-weight undiagnosed type 2 diabetes postmenopausal women report that parity was not significantly associated with increased risk of metabolic syndrome. However, the odds of metabolic risk factor such abdominal obesity was significantly associated with multiparity in normal weight Chinese women 47 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Shi et al 47 in a cross-sectional analysis of normal-weight undiagnosed type 2 diabetes postmenopausal women report that parity was not significantly associated with increased risk of metabolic syndrome. However, the odds of metabolic risk factor such abdominal obesity was significantly associated with multiparity in normal weight Chinese women 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that significantly affected the overall and abdominal obesity (except for WHR) of the study sample seems to be parity, with significantly higher general and abdominal obesity levels in women with kids. Although the influence of parity on obesity is still controversial in the emerging literature [ 27 , 48 ], Bladeau et al [ 49 ] attested to an increase in abdominal adipose tissue with increasing parity. The prevalence of overall and central obesity was significantly lower (except for WHR) in female graduates than in women with lower levels of education, according to previous studies [ 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that parity was remarkably associated with the risk of carotid atherosclerotic plaque, and also associated with a decrease of HDL-C and an increase of the ratio of blood glucose/insulin [ 20 , 21 ]. In addition, multiple parturition could increase the risk of metabolic syndrome in women, and thus, it might result in the increased risk of ICVD in postmenopausal women to a certain extent [ 22 , 23 ]. Active or passive smoking, as a bad habit of life, has been found to be an independent risk factor for cardiovascular disease and also an important risk factor for adult death in our country [ 24 27 ].…”
Section: Discussionmentioning
confidence: 99%